EVALUATION OF THE EFFECTIVENESS OF DRY NEEDLING IN REDUCING MYOFASCIAL PAIN ASSOCIATED WITH TEMPOROMANDIBULAR JOINT DISORDERS - V.V. Davydenko (Український стоматологічний альманах, 2024)
Background. The high prevalence of temporomandibular joint disorders, which, according to various sources, ranges from 7% to 30%, necessitates to develop and implement effective minimally invasive treatment methods. Myofascial pain often accompanies temporomandibular joint disorders. In dental practice, myofascial pain primarily arises from hypertonicity of the masticatory and facial muscles, often linked to bite pathology, a history of bruxism, and other related factors.